Bark and wood boring insects involved in oak declines in Europe: Current knowledge and future prospects in a context of climate change - Sallé, A; Nageleisen, L.-M.; Lieutier, F (Forest Ecology and Management, 2014)
Oak declines are multifactorial processes in which bark and wood boring (BWB) beetles can act as major inciting factors, killing the weakened trees. Nonetheless, the current knowledge on the biology, ecology of these species is scattered and no efficient management strategies are currently available. Based on the existing literature and field observations from the French forest health service, we firstly identified the prominent BWB species implicated in oak declines in Europe. Secondly we performed a state of the art on the biology and ecology of these species, with a particular reference to the interactions with their host trees. Finally considerations were made on how climate change could affect these interactions. Six species, namely Agrilus biguttatus, Coraebus florentinus, Coraebus undatus, Cerambyx cerdo, Platypus cylindrus and Scolytus intricatus are frequently implicated in oak declines in Europe. The interactions with their hosts regarding selection and resistance are generally poorly known. Likewise, these beetles are associated with a diverse microbial community, which composition and implication in the biology of insects and decline processes is unclear in most cases. Climate change will probably increase the frequency and distribution of oak declines in Europe. It will also likely modify the interactions between oaks and these beetles by promoting contributing factors of decline, modifying directly and indirectly host resistance, phenology and attractiveness, and beetles development, distribution and interaction with microorganisms. Evidences point out that the increase in temperature has already favored the distribution and development of C. florentinus and could enhance the development of other species. Potential research prospects are proposed, aiming at acquiring missing basic knowledge and improving the currently limited management strategies.
Keywords: associated microorganisms; Host resistance; management strategies; Thermal requirements

Microrganismos Associados à Cortiça em Diferentes Fases da sua Fileira - Santos, Maria Natércia; Bragança, Maria Helena; Casimiro, Pedro Piloto (Silva Lusitana, 2005)
Several microorganisms have been considered responsible for decrease in cork quality and wine off - flavours. To improve the knowledge on cork microbiology throughout the tree to end product (stopper) steps, the work developed included two components. The first, on fungal populations colonising the tree, aims to evaluate the probable role of the tree as source of both slab and stopper contamination. The second focusing the collection of dispersed information about the microbial populations, throughout the industrial cork steps, has a main objective to constitute a basis for the delineation of further studies on this matter. The integration of results allows the following conclusions: (i) the microbial populations change throughout cork manufacture process, reflecting both the different environmental conditions and methods used; (ii) the persistence of a large part of these populations throughout the several phases (tree to end product), indicates that the tree is, probably one of the most important microorganism source; (iii) a fraction of these populations included in the group are pointed out as capable of producing secondary metabolites that affect both cork and wine quality; (iv) no significant differences between microbial population diversity and tree vigour level were found. The results obtained did not allow a relationship between decrease of tree vigour and wine-off flavours. Dispersed and sometimes inaccurate information makes it difficult to build a consistent knowledge frame, indicating that a well - balanced multidiscipline research program including all the partners involved in cork processing, is an urgent necessity.
Keywords: associated microorganisms; Cork oak; cork stopper manufacture

Microrganismos Associados à Cortiça em Diferentes Fases da sua Fileira - Santos, Maria Natércia; Bragança, Maria Helena; Casimiro, Pedro Piloto (Silva Lusitana, 2005)
Several microorganisms have been considered responsible for decrease in cork quality and wine off - flavours. To improve the knowledge on cork microbiology throughout the tree to end product (stopper) steps, the work developed included two components. The first, on fungal populations colonising the tree, aims to evaluate the probable role of the tree as source of both slab and stopper contamination. The second focusing the collection of dispersed information about the microbial populations, throughout the industrial cork steps, has a main objective to constitute a basis for the delineation of further studies on this matter. The integration of results allows the following conclusions: (i) the microbial populations change throughout cork manufacture process, reflecting both the different environmental conditions and methods used; (ii) the persistence of a large part of these populations throughout the several phases (tree to end product), indicates that the tree is, probably one of the most important microorganism source; (iii) a fraction of these populations included in the group are pointed out as capable of producing secondary metabolites that affect both cork and wine quality; (iv) no significant differences between microbial population diversity and tree vigour level were found. The results obtained did not allow a relationship between decrease of tree vigour and wine-off flavours. Dispersed and sometimes inaccurate information makes it difficult to build a consistent knowledge frame, indicating that a well - balanced multidiscipline research program including all the partners involved in cork processing, is an urgent necessity.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: associated microorganisms; Cork oak; cork stopper manufacture